Minilaparotomy for excision of a functioning noncommunicating rudimentary horn and endometrioma in a patient with solitary kidney: A case report - Amany Abd El-Wadoud Makroum; Mahmoud Mohamed Abdelrazik; Maher Shams El-Deen Hassan (Wolters Kluwer Medknow Publications, 2020)
Müllerian duct anomalies result from abnormal formation, fusion, or reabsorption of the Müllerian ducts during fetal life. A close embryologic relation exists between the development of the urinary and reproductive organs. Hence, renal tract defects are likely to be found in women with congenital uterine malformation. This report describes the technique of minilaparotomy for the removal of a noncommunicating rudimentary horn together with an associated endometrioma in a patient with absent one kidney.